1993
DOI: 10.1002/jmv.1890400414
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IgA class antibody to hepatitis E virus in serum samples from patients with hepatitis E virus infection

Abstract: A newly developed assay for IgA class antibody to hepatitis E virus (IgA anti-HEV) was used to study 145 serum samples collected during an outbreak of an enterically transmitted hepatitis that occurred in 3 villages in the lower Shebeli region of Southern Somalia between January, 1988 and November, 1989. A total of 52.4% of the afflicted patients were found positive for IgA anti-HEV, and 73.1% of these were also positive for IgM. Both antibodies disappeared during the convalescence period. Similar results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 21 publications
1
24
0
2
Order By: Relevance
“…Therefore, in the present study, we chose the solid-phase ELISA format for detecting anti-HEV antibodies. It has been reported that anti-HEV IgA can be utilized as an additional confirmatory antibody for recent HEV infection (2). Although the presence of a specific antibody of the IgA class is diagnostic for recent infection in several viral or nonviral diseases, including type A, type B, or type C acute hepatitis (28,35,57), as well as Chlamydia trachomatis infection, Chlamydia pneumoniae infection, and cholera (26,33,51), the clinical and epidemiological significance of positivity for anti-HEV IgA remains to be fully verified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in the present study, we chose the solid-phase ELISA format for detecting anti-HEV antibodies. It has been reported that anti-HEV IgA can be utilized as an additional confirmatory antibody for recent HEV infection (2). Although the presence of a specific antibody of the IgA class is diagnostic for recent infection in several viral or nonviral diseases, including type A, type B, or type C acute hepatitis (28,35,57), as well as Chlamydia trachomatis infection, Chlamydia pneumoniae infection, and cholera (26,33,51), the clinical and epidemiological significance of positivity for anti-HEV IgA remains to be fully verified.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoglobulin M (IgM) class of antibody against HEV (anti-HEV IgM) is used as a reliable and sensitive marker of recent HEV infection (2)(3)(4)38). However, the specificity of the solid-phase assay for anti-HEV IgM has been questioned in some cases, particularly in patients with IgMrheumatoid factors in the serum, which have activity against the Fc portion of IgG directed to HEV antigen and may elicit a false-positive result (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At least 50% of cases of sporadic hepatitis admitted to military hospitals in Rawalpindi, Pakistan, are non-A, non-B hepatitis (presumably hepatitis E). [25][26][27][28] In 1993−1994, a large outbreak of hepatitis E occurred in Islamabad, the capital of Pakistan, as a result of contamination from a malfunctioning water treatment plant. Almost 4,000 cases were reported 20 .…”
Section: Discussionmentioning
confidence: 99%
“…As for anti-HEV IgA antibodies, it is unclear whether our assay is detecting both dimeric secretory IgA and monomeric IgA. However, it seems that anti-HEV IgA antibodies can be utilized as an additional confirmatory antibody for recent HEV infection, as suggested by Chau et al (1993) who detected anti-HEV IgA antibodies in serum samples obtained from patients who had acute waterborne hepatitis in southern Somalia and Pakistan.…”
mentioning
confidence: 94%